A specific SNP-based multiplex PCR assay for the simultaneous identification of two biological ingredients for the Chinese patent medicine, Danggui Buxue pill - Liu, Yinrong; Yang, Yingying; Zhou, Zishan; Fan, Jia’er; Diao, Jianxin; Chao, Zhi; Tian, Enwei (Frontiers in Pharmacology, 2023)
Background: More and more Chinese patent medicines (CPM) have been widely used in East Asian and North American countries, and the safety and efficacy of CPM have highly attracted public attentions. However, it is difficult to supervise the authenticity of the multiple biological ingredients within CPM according to the microscopic inspection, physical and chemical detection. As the raw materials may have similar characteristics of tissue structures and ergastic substances, or similar chemical composition and contents when substitutes and/or adulterants feed. DNA molecular marker have been used to distinguish the biological ingredients within CPM based on conventional PCR assay. However, it was proved to be time and labor consuming and reagents wasting, as many times’ operations of PCR amplification were required for identifying the complex species composition within CPM. Here, we took the CPM (Danggui Buxue Pill) as an example, and aimed to establish a specific-SNP based multiplex PCR assay and simultaneously determine the authenticity of the two biological ingredients (Angelicae Sinensis Radix and Astragali Radix) within this CPM. Methods: We respectively designed the species-specific primers based on a highly variable nrITS for discriminating Angelicae Sinensis Radix and Astragali Radix from their common substitutes and adulterants. Specificity of the primers was checked through conventional PCR assay and multiplex PCR assay. Further, we used a handcrafted Danggui Buxue Pill sample (DGBXP) to optimize annealing temperatures for the primers with multiplex PCR, and the sensitivity was also assessed. Finally, fourteen batches of commercial Danggui Buxue pill were used to verify the stability and practicability of the established multiplex PCR assay. Results: Two pairs of highly species-specific primers for amplifying Angelicae Sinensis Radix and Astragali Radix were respectively screened, and our established multiplex PCR assay showed a high specificity and sensitivity (lowest detection concentration: 4.0×10-3 ng/μL) at optimal annealing temperature of 65℃. The method could simultaneously identify both biological ingredients within the Danggui Buxue Pill. Conclusion: The specific-SNP based multiplex PCR provided a simple, time and labor-saving method for simultaneous identification of the two biological ingredients within Danggui Buxue Pill. This study was expected to provide a novel qualitative quality control strategy for CPM.